2015
DOI: 10.1039/c5cp02563j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of brown carbon (BrC) chromophores in secondary organic aerosol generated from photo-oxidation of toluene

Abstract: Atmospheric brown carbon (BrC) is a significant contributor to light absorption and climate forcing. However, little is known about a fundamental relationship between the chemical composition of BrC and its optical properties. In this work, light-absorbing secondary organic aerosol (SOA) was generated in the PNNL chamber from toluene photo-oxidation in the presence of NOx (Tol-SOA). Molecular structures of BrC components were examined using nanospray desorption electrospray ionization (nano-DESI) and liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
355
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 251 publications
(379 citation statements)
references
References 88 publications
22
355
0
2
Order By: Relevance
“…The low-NO x mass spectrum shown in Fig. 1 is qualitatively similar to the low-NO x mass spectrum of toluene SOA discussed in a previous study in which it was prepared in a different smog chamber but analyzed by the same nano-DESI instrument (Lin et al, 2015).…”
Section: Resultssupporting
confidence: 58%
“…The low-NO x mass spectrum shown in Fig. 1 is qualitatively similar to the low-NO x mass spectrum of toluene SOA discussed in a previous study in which it was prepared in a different smog chamber but analyzed by the same nano-DESI instrument (Lin et al, 2015).…”
Section: Resultssupporting
confidence: 58%
“…This work also demonstrates the need for additional research to determine the extent of in-fog formation of CHO, CHOS, CHNO, and CHNOS species. The formation of these species can result in increased organic aerosol mass formation (McNeill et al, 2012) and absorption of ultraviolet and visible light by aerosol (Lin et al, 2015), both of which are important for climate and air quality. The regional O&NG processing VOC emissions observed in this study are likely to be precursors for the CHO, CHOS and CHNOS species.…”
Section: Discussionmentioning
confidence: 99%
“…Potential sources of BrC include emissions from biomass burning (Kirchstetter et al, 2004;Moosmüller et al, 2009;Chen and Bond, 2010;Lack et al, 2012a;Saleh et al, 2014;Washenfelder et al, 2015); incomplete combustion of fossil fuels, especially coal (Bond, 2001;Yang et al, 2009;Olson et al, 2015); and secondary organic aerosols (Saleh et al, 2013;Zhang et al, 2013;Lin et al, 2015). There exists significant uncertainty concerning the relative contribution of each of these source types to total BrC concentrations, but several studies have identified biomass burning as a potentially significant source (Washenfelder et al, 2015;McMeeking et al, 2014;Lack et al, 2012a).…”
mentioning
confidence: 99%